The prevalence and risk of allergic rhinitis in psoriasis patients: a systematic review and meta-analysis - Suvijak Untaaveesup; Thipsukon Amnartpanich; Nattawut Leelakanok; Weerapat Owattanapanich; Piyawat Kantagowit; Wichapol Dendumrongsup; Supawich Sornwanee; Pornteera Srichana; Walaiorn Pratchyapruit; Wannada Laisuan (Scientific Reports)
Abstract Psoriasis, a chronic inflammatory systemic disease, may increase the risk of allergic diseases. This meta-analysis assesses the prevalence and risk of developing allergic rhinitis in psoriasis. We systematically searched MEDLINE, Scopus, and EMBASE for population-based studies documenting AR in psoriasis compared to those without from inception to December 2023. Meta-analysis was conducted using the random-effects model. Eight studies, comprising 5 cross-sectional studies, 1 case-control study, 1 retrospective cohort study, and 1 prospective cohort study, were included. The increased prevalence of AR was 22.29% (95% CI: 0.135 to 0.281; P < 0.001; I2 = 99.05%) in the psoriasis population. The AR risk in psoriasis was insignificant (adjusted OR 1.19%; 95% CI: 0.69 to 2.06; I2 = 99%; P < 0.00001). Subgroup analysis in moderate to severe psoriasis cases revealed a trend of higher risk of AR (OR 1.41%; 95% CI: 0.94 to 2.10; I2 = 92%; P = 0.0003) with very low certainty of evidence. High heterogeneity was observed in most analyses. Our meta-analysis demonstrated a higher prevalence of AR in psoriasis patients. Evaluating and treating allergic diseases can enhance holistic treatment.